The Effect of Budget Planning, Budget Implementation, and Human Resource Competencies on Budget Realization at Ganesha University of Education - Kadek Sri Handayani; Ni Kadek Sinarwati; Putu Indah Rahmawati (Universitas Pendidikan Ganesha, 2022)
The budget is an important component in implementing public services whose implementation is left to ministries/agencies and work units for the benefit of the community. However, much has not been achieved in its implementation due to the realization that budget absorption is not optimal. This study analyzes the impact of budget planning, budget execution, and human resource competence on budget absorption. This type of research is associative research. The population in this study was 58 budget management employees. The sample used is saturated. The data in this study are primary data and secondary data. Data collection techniques used questionnaires and in-depth interviews. Data analysis techniques used multiple linear regression analysis. The study results show that budget planning has a significance score of 0.154 > 0.05. It shows that H1 is rejected, meaning that budget planning has no significant effect on budget absorption. Second, budget execution has a significance score of 0.000 <0.05. It shows that H2 is accepted, meaning that budget execution significantly affects budget absorption. Third, the human resource competency variable has a significance score of 0.018 <0.05. It shows that H3 is accepted, meaning that human resource competence significantly affects budget absorption. This study shows that budget planning, execution, and human resource competence do not affect budget absorption.